(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Studies suggest a possible inverse correlation between smoking attitude and happiness levels. The present paper investigates the relation between males and females smoking prevalence and thriving levels in 155 countries worldwide. Analyses, after adjusting for socio-economic factors, reveal a different relationship between happiness and prevalence of tobacco smoking in the two genders. Countries with highest prevalence of males smoking show the lowest wellbeing levels (Beta coefficient: -0.350; P Value <0.001) while countries with highest prevalence of females smoking show the highest levels of wellbeing (Beta coefficient: 0.144; P Value: 0.030). The countries with the highest prevalence of people thriving are those with the highest prevalence of women smoking and the lowest prevalence of males smoking.